2022
DOI: 10.3390/plants11050672
|View full text |Cite
|
Sign up to set email alerts
|

The Halophyte Species Solanum chilense Dun. Maintains Its Reproduction despite Sodium Accumulation in Its Floral Organs

Abstract: Salinity is a growing global concern that affects the yield of crop species, including tomato (Solanum lycopersicum). Its wild relative Solanum chilense was reported to have halophyte properties. We compared salt resistance of both species during the reproductive phase, with a special focus on sodium localization in the flowers. Plants were exposed to NaCl from the seedling stage. Salinity decreased the number of inflorescences in both species but the number of flowers per inflorescence and sepal length only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 104 publications
(148 reference statements)
0
3
1
Order By: Relevance
“…Na + content was increased in roots and fruits by a ratio of 2.94 and 1.45, respectively, as compared with fresh water-irrigated plants (Figure 3a,b). It is reported that sodium ions could accumulate in inflorescences, pericarp, and even in tomato seeds under salinity stress, however, in higher amounts compared with data produced in this study [52,53]. Although fruits (the marketable part of the tomato) accumulated more sodium ions under a saline irrigation regime of 3000 ppm NaCl (no BC, 77.8 mg/100 gm), the sodium level in dried fruits was below the risk threshold according to USDA health standards [54].…”
Section: Soil Propertiescontrasting
confidence: 60%
“…Na + content was increased in roots and fruits by a ratio of 2.94 and 1.45, respectively, as compared with fresh water-irrigated plants (Figure 3a,b). It is reported that sodium ions could accumulate in inflorescences, pericarp, and even in tomato seeds under salinity stress, however, in higher amounts compared with data produced in this study [52,53]. Although fruits (the marketable part of the tomato) accumulated more sodium ions under a saline irrigation regime of 3000 ppm NaCl (no BC, 77.8 mg/100 gm), the sodium level in dried fruits was below the risk threshold according to USDA health standards [54].…”
Section: Soil Propertiescontrasting
confidence: 60%
“…For instance, salt-tolerant wild relatives of tomato, such as S. chilense and S. pennellii , exhibit significantly higher leaf Na + content compared to their more sensitive counterpart, S. lycopersicum - up to ten-fold higher in the case of S. chilense [5,7]. These species seem to have a different strategy from S. lycopersicum , maintaining high levels of sodium leaf content, but investing more in sodium sequestration as suggested by an increased expression of tonoplast-localised NHX-type Na + /H + exchangers compared to their homologues in cultivated tomato [5,7]. In such species, the high accumulation of Na + in the leaves acts as a cheap osmoticum to minimise the high energy cost of osmolyte synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Native to western South America, numerous wild relatives of tomato, such as S. pennellii, S. chilense, and S. cheesmaniae, are adapted to saline environments. Notably, these species have demonstrated higher salinity tolerance than S. lycopersicum [5][6][7], indicating a promising avenue for identifying salt resistance genes and quantitative trait loci (QTLs).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bigot et al [ 27 ] also compared the salt resistance of a crop, tomato ( Solanum lycopersicum ), and a wild relative, S. chilense (Solanaceae), focusing on the reproductive phase, particularly Na localisation in floral organs. Salinity was found to affect reproductive development in the two species, but in different ways.…”
Section: Special Issue Contentsmentioning
confidence: 99%